A Timely Synthetic Tailoring of Biaxially Extended Thienylenevinylene‐Like Polymers for Systematic Investigation on Field‐Effect Transistors. (8th December 2014) - Yoo, Dohyuk; Nketia‐Yawson, Benjamin; Kang, Seok‐Ju; Ahn, Hyungju; Shin, Tae Joo; Noh, Yong‐Young; Yang, Changduk
<x xml:space="preserve">Abstract</x> Considering there is growing interest in the superior charge transport in the (E)‐2‐(2‐(thiophen‐2‐yl)‐vinyl)thiophene (TVT)‐based polymer family, an essential step forward is to provide a deep and comprehensive understanding of the structure–property relationships with their polymer analogs. Herein, a carefully chosen set of DPP‐TVT‐n polymers are reported here, involving TVT and diketopyrrolopyrrole (DPP) units that are constructed in combination with varying thiophene content in the repeat units, where n is the number of thiophene spacer units. Their OFET characteristics demonstrate ambipolar behavior; in particular, with DPP‐TVT‐0 a nearly balanced hole and electron transport are observed. Interestingly, the majority of the charge‐transport properties changed from ambipolar to p‐type dominant, together with the enhanced hole mobilities, as the electron‐donating thiophene spacers are introduced. Although both the lamellar d‐spacings and π‐stacking distances of DPP‐TVT‐n decreased with as the number of thiophene spacers increased, DPP‐TVT‐1 clearly shows the highest hole mobility (up to 2.96 cm2 V−1 s−1) owing to the unique structural conformations derived from its smaller paracrystalline distortion parameter and narrower plane distribution relative to the others. These in‐depth studies should uncover the underlying structure–property relationships in a relevant class of TVT‐like semiconductors, shedding light on the future design of top‐performing semiconducting polymers.